Boosting Students’ Skimming Reading Skill by Using Cooperative Integrated Reading and Composition (CIRC) Learning Method - SULIHATI; Misnawati (Journal of English Education and Social Science, 2022)
The title of this thesis is Boosting students’ skimming reading skill by using Cooperative Integrated Reading and Composition (CIRC ) Learning Method (A Collaborative Classroom Action Research to the Second Year Students of SMAN 1 Samalanga). The researcher put two problems of this research with the questions as follow: first, how does CIRC method improvement the second-year students of SMAN 1 Samalanga in skimming reading skill? Second, how do the students respond toward CIRC method in teaching learning process of skimming reading skill of the second-year students’ of SMAN 1 Samalanga? Based on the research problems, the purpose of this research were: first, to know the CIRC method improvement the second year students of SMAN 1 Samalanga in skimming reading skill, and second, to know the students’ skimming reading skill by using CIRC learning method. This research was a collaborative classroom action research. The research subject was the second-year students of SMAN 1 Samalanga. The sample of this research 30 students. The data was collected through the reading test, students’ observation checklist, teacher’s observation checklist and questionnaire. The data was analyzed through the descriptive qualitative research. After the researcher was done all the steps of action research (cycle 1 and cycle II) the students’ mean score increased from 60 in cycle 1 and became 80 in cycle II. Besides, from the observation checklist to the students’ activity, it was found the percentage of the students’ participation during teaching learning process in reading class increased gradually. It was proved by the result of the observation checklist were taken at the beginning of cycle 1, the percentage of the students’ participation was only 54 and became 70 in cycle II. And also, the list of questionnaires given to the students indicates that the students had positive respond toward the implementation of CIRC method in reading class. It was provided by overall mean score 3,9 that was categorized to the level of Agree.